Assessment of full life-cycle air emissions of alternative shipping fuels. (20th January 2018) - Gilbert, Paul; Walsh, Conor; Traut, Michael; Kesieme, Uchenna; Pazouki, Kayvan; Murphy, Alan
Abstract: There is a need for alternative fuels in the shipping sector for two main motivations: to deliver a reduction in local pollutants and comply with existing regulation; and to mitigate climate change and cut greenhouse gas emissions. However, any alternative fuel must meet a range of criteria to become a viable option. Key among them is the requirement that it can deliver emissions reductions over its full life-cycle. For a set of fuels, comprising both conventional and alternative fuels, together with associated production pathways, this paper presents a life-cycle assessment with respect to six emissions species: local pollutants sulphur oxides, nitrogen oxides, and particulate matter; and greenhouse gases carbon dioxide, methane, and nitrous oxide. While the analysis demonstrates that no widely available fuel exists currently to deliver on both motivations, some alternative fuel options have the potential, if key barriers can be overcome. Hydrogen or other synthetic fuels rely on decarbonisation of both energy input to production and other feedstock materials to deliver reductions in greenhouse gas emissions. Similarly, bio-derived fuels can be an abatement option, but only if it can be ensured that land-use change whilst growing biomass does not impact wider potential savings and the sector is able to compete sufficiently for their use. These examples show that crucial barriers are located upstream in the respective fuel life-cycle and that the way to overcome them may reside beyond the scope of the shipping sector alone. Highlights: Alternative shipping fuels are needed to manage climate change and local pollutants. LCA is used to quantify environmental impacts of current and future fuels. There is no widely available fuel to manage climate change and local pollutants. Hydrogen and biofuels have significant impacts upstream in the fuel life-cycle. Minimising these impacts may reside beyond the scope of the shipping sector alone.